Intergroups Conflict Patterns - Doina I. POPESCU (Revista de Management Comparat International)
In the endeavour of explaining the causes and mechanisms which fundament the emergence of conflicts, researchers have elaborated theoretical conflict patterns. Some researchers consider that conflict patterns describe either the process or the structure of a contrariety situation. Through the process pattern, there are identified events which characterize a conflict and the succession connection between different stages. Structural patterns define favourable conditions and describe the way in which they influence the conflictual behaviour. Another group of patterns have the purpose of describing organizational conflicts. Among the conflict patterns, the ones which have special importance from both a managerial theoretical and practical point of view are the following: process pattern, structural pattern and organizational pattern. Also, the paper describes the ways for managing the conflicts and the process of negotiation.